# SOLUTION: solve using the substitution method. Answer in solution set. 2x+y=0 6x-3y=12

Algebra ->  Algebra  -> Customizable Word Problem Solvers  -> Mixtures -> SOLUTION: solve using the substitution method. Answer in solution set. 2x+y=0 6x-3y=12      Log On

 Ad: Over 600 Algebra Word Problems at edhelper.com Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Word Problems: Mixtures Solvers Lessons Answers archive Quiz In Depth

 Question 592567: solve using the substitution method. Answer in solution set. 2x+y=0 6x-3y=12Found 2 solutions by stanbon, solver91311:Answer by stanbon(57967)   (Show Source): You can put this solution on YOUR website!solve using the substitution method. Answer in solution set. 2x+y=0 6x-3y=12 ----- y = -2x Substitute: 6x - 3(-2x) = 12 6x + 6x = 12 12x = 12 x = 1 --------- Solve for "y": y = -2x y = -2*1 = -2 =========================== Cheers, Stan H. ================= Answer by solver91311(17077)   (Show Source): You can put this solution on YOUR website! Solve the first equation for which is to say, add to both sides of the first equation. Once you have an expression in that is equal to , substitute it into the second equation in place of the . Solve the resulting single variable equation for . Once you have a value for , substitute that value in place of in either equation. Solve the resulting single variable equation in for . Express your answer as an ordered pair of the form using the values determined in the steps above. John My calculator said it, I believe it, that settles it